Discovery of benzofuran propanoic acid GPR120 agonists: From uHTS hit to mechanism-based pharmacodynamic effects. Issue 23 (1st December 2016) - Lombardo, Matthew; Bender, Kate; London, Clare; Kirkland, Melissa; Mane, Joel; Pachanski, Michele; Geissler, Wayne; Cummings, John; Habulihaz, Bahanu; Akiyama, Taro E.; Di Salvo, Jerry; Madeira, Maria; et al.
Graphical abstract: Abstract: The transformation of an aryloxybutanoic acid ultra high-throughput screening (uHTS) hit into a potent and selective series of G-protein coupled receptor 120 (GPR120) agonists is reported. uHTS hit1 demonstrated an excellent rodent pharmacokinetic profile and selectivity over the related fatty acid receptor GPR40, but only modest GPR120 potency. Optimization of the "left-hand" aryl group led to compound6, which demonstrated a GPR120 mechanism-based pharmacodynamic effect in a mouse oral glucose tolerance test (oGTT). Further optimization gave rise to the benzofuran propanoic acid series (exemplified by compound37 ), which demonstrated acute mechanism-based pharmacodynamic effects. The combination of in vivo efficacy and attractive rodent pharmacodynamic profiles suggests compounds generated from this series may afford attractive candidates for the treatment of Type 2 diabetes.